Islamic Philosophy and Minangkabau Customs: Practice in Sarugo Society - Fithri, Widia; Hadi, Rahmad Tri; Mawaddah, Arini Alfa (UIN Maulana Malik Ibrahim Malang, 2023)
The Minangkabau people are deeply committed to preserving their customs and culture, which are based on Islamic law, one of which is manifested through the Gadang house. However, the function and meaning of the Gadang house are gradually declining, which naturally affects the continued survival as a symbol and philosophy of the Minangkabau Muslim community. This is field research with a qualitative method. Primary data was obtained from interviews, observation, and documentation. The secondary sources referred to books, journals, and other documents. This research found that Gadang house, which is preserved from generation to generation, combines Islamic values and the life philosophy of the Minangkabau community. From the architectural aspect of the building, the gadang houses in Sarugo village are arranged in rows like prayer lines, all facing toward the mosque. Besides, various Islamic activities, such as weekly dhikr activities, khatam Qur'an for elementary schoolers, events for the maulid nabi, commemoration of Isra' Mikraj, and active recitation of Surah Yasin (yasinan). Correspondingly, the activities of the Batagak Pangulu, wedding ceremonies, and death funerals are held according to Islamic law and customs. Masyarakat Minangkabau memiliki komitmen yang tinggi dalam melestarikan adat dan budaya yang berlandaskan syariat Islam. Salah satunya dimanifestasikan melalui keberadaan rumah Gadang. Namun, fungsi dan makna rumah Gadang saat ini terus mengalami penyusutan, hal tersebut tentu berdampak pada eksistensi rumah gadang sebagai simbol dan filosofi masyarakat Muslim Minangkabau. Jenis penelitian ini field research dengan metode yang digunakan kualitatif. Sumber data primer diperoleh dari wawancara, observasi dan dokumentasi. Sumber sekunder penelitian ini merujuk kepada buku, jurnal, dan lain sebagainya. Penelitian ini menemukan keberadaan rumah Gadang yang dipelihara secara turun temurun yang memadukan nilai-nilai Islam dan falsafah hidup masyarakat Minangkabau. Pertama, dari aspek arsitektur bangunannya. Rumah Gadang di kampung Sarugo disusun bershaf-shaf seperti shaf dalam shalat yang semuanya menghadap ke arah masjid. Kedua, berbagai kegiatan keislaman seperti kegiatan mingguan wirid pengajian, khatam Qur`an untuk anak-anak tingkat SD, acara maulid nabi, peringatan Isra’ Mikraj, serta yasinan. Demikian juga dengan kegiatan batagak pangulu, pernikahan, serta kematian diselenggarakan sesuai syariat Islam dan adat.